Community water quality monitoring - Nur Diyana, Mohd Samsuddin (2012)
Malaysians receive drinking water every day from their public water systems, which may be publicly or privately owned. There are a number of health risks from drinking water if not properly treated or disinfected, or if distributed through an improper maintenance of distribution system. In this study, six stations of drinking water sources in Kuantan and Gambang area were sampled and analyzed for their water quality parameters, including pH, dissolved oxygen, total dissolved solid, hardness, chemical oxygen demand, biochemical oxygen demand, heavy metals and anions. Standard methods were used to measure each of parameters. Results were evaluated based on National Drinking Water Quality Standards for Malaysia. The concentration of all contaminants was within the levels recommended by National Drinking Water Quality Standards. As a conclusion, drinking water in Kuantan and Gambang area were considered safe to consume.